Contemporary architects - Morgan, Ann Lee; Naylor, Colin (Contemporary arts series, 1987)
"To strengthen the contemporary focus of this volume, we have added about forty architects and have deleted some whose activity ceased before World War II. In making these decisions, we have been assisted by an Advisory Board. As in the first volume, we have continued to define the word "architect" very broadly, so as to include planners, theorists, structural engineers, and landscape architects whose work seems to be central to the enterprise of creating habitable spaces in our day."--Editor's note.